ASURANSI KONVENSIONAL DAN ASURANSI SYARIAH DALAM HUKUM ISLAM KONTEMPORER - Ana Lathifatul Hanifah (LPPM STAI DARUSSALAM LAMPUNG, 2017)
The paper is about conventional insurance and takaful insurance in contemporary Islamic law. Insurance is one of the non bank financial institution that function to collect public funds to provide protection against the risk of uncertainty resulting from the occurence of accidentns, accidents or other losses. Insurance based on the operational system is divided into two types, namely conventional insurance and takaful insurance. Takaful Insurance is classified as a new non-bank financial institution innovation and based on the principles of Islam, the Takaful is still not known by the people of Indonesia whose population is mostly Muslim. Of the phenomenon the authors try to discuss about conventional insurance and takaful insurance in contemporary islamic law.